The Effect of Financial Risk and Capital Structure on the Financial Performance of Banks on the Indonesian Stock Exchange - Fathin Hairiyah; Muhammad Nabil Kayana; Farah Margaretha Leon (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The impact of capital structure and financial risk on the financial performance of banks listed on the Indonesia Stock Exchange is examined in this study. The primary question posed is how profitability as determined by return on assets is impacted by liquidity risk, credit risk, operational risk, leverage, and net interest margin. In order to give a thorough grasp of the elements influencing bank performance, this study aims to investigate the relationships between these variables. Banks' yearly financial reports for the 2020–2024 period are subjected to panel data regression analysis as part of the quantitative research methodology. The addition of net interest margin as a variable that mediates the association between financial risk and profitability is what makes this study novel. It is anticipated that the study's findings will demonstrate how effective capital structure management and financial risk reduction can boost bank profitability. The significance of an integrated risk management strategy is emphasized in the study's conclusion. The implications of the study provide practical recommendations for financial managers, investors, and regulators, and open up space for further research on external factors that affect banking performance.